2003
DOI: 10.1309/42f0-0d0d-jd0j-5edt
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression in Estrogen Receptor-Negative Breast Cancer Immunohistochemical, Clinical, and Prognostic Associations

Abstract: We sought to determine the prevalence of androgen receptor (AR) expression in a predominantly estrogen receptor (ER)-negative subset of breast cancers and delineate the immunohistochemical and clinical associations, including whether AR expression has prognostic significance in ER-negative tumors. We identified 69 ER-negative and 19 ER-positive breast cancer cases with concurrent immunohistochemical prognostic panels (ER, PR, HER-2/neu, Ki-67, and p53); immunohistochemical analysis was performed for AR using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
157
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(179 citation statements)
references
References 13 publications
17
157
3
2
Order By: Relevance
“…AR typically is present in a greater proportion of breast tumors (80-90%) than ERa (50-80%; reviewed in refs. 5,9) and previous studies have indicated the potential for AR to predict disease progression (10,11). In addition, we have reported that the level of the AR predicts both the likelihood and the duration of response to therapy with the synthetic progestin, medroxyprogesterone acetate (12), and that disease progression after medroxyprogesterone acetate therapy is associated with inactivating mutations in the AR gene (13).…”
Section: Introductionmentioning
confidence: 59%
“…AR typically is present in a greater proportion of breast tumors (80-90%) than ERa (50-80%; reviewed in refs. 5,9) and previous studies have indicated the potential for AR to predict disease progression (10,11). In addition, we have reported that the level of the AR predicts both the likelihood and the duration of response to therapy with the synthetic progestin, medroxyprogesterone acetate (12), and that disease progression after medroxyprogesterone acetate therapy is associated with inactivating mutations in the AR gene (13).…”
Section: Introductionmentioning
confidence: 59%
“…AR expression in ERa-negative breast cancer is correlated with a lower Nottingham grade and apocrine differentiation (Niemeier et al 2010). The association between AR and survival is not so clear in ERa-negative breast cancers as in ERa-positive breast cancers; studies have reported either no association (Gonzalez et al 2008, Peters et al 2009, Park et al 2011 or an association with improved survival (Agoff et al 2003, Luo et al 2010, Witzel et al 2013). In addition, one meta-analysis reported that AR is associated with improved overall survival in ERa-negative breast cancer (Qu et al 2013), while the other reported no association (Vera-Badillo et al 2014).…”
Section: Era-negative Breast Cancermentioning
confidence: 99%
“…DHT induced p53 expression in MCF7 breast cancer cells (Wang et al 2013a,b), while AR expression has been associated with a lack of p53 expression in unselected human breast cancers (Ogawa et al 2008). However, in a different cohort that was separated into ERa-positive or ERa-negative disease, no association between AR and p53 was observed in either group (Agoff et al 2003). Therefore, while there is some evidence to support the functional interactions among AR, PTEN and p53, further studies are required to clarify the role of this pathway in breast cancer cells.…”
Section: Ar Pten P53 and Pi3k/aktmentioning
confidence: 99%
“…However, it is currently unclear how to stratify individual breast cancers based on whether they will respond favourably to androgen treatment or not. In different breast cancer cell lines, modulation of androgen signalling can have growth-inhibitory or growth-promoting effects (Birrell et al 1995, Ortmann et al 2002, Greeve et al 2004, Lyu et al 2014, reviewed in Fioretti et al (2014), and this extends to the applicability of AR expression as a prognostic marker in specific subtypes of breast cancer (Kuenen-Boumeester et al 1996, Agoff et al 2003, Peters et al 2009, Kraus et al 2010, Gasparini et al 2014. Such conflicting reports/data raise concerns for the clinical efficacy of androgen modulation in breast cancer.…”
Section: Ar Expression In Mammary Epitheliummentioning
confidence: 99%